Physical Fatigue Perawat Saat Bekerja di Ruang Intensive Care Unit - Hammad Hammad (Poltekkes Kemenkes Mataram, 2021)
Physical Fatigue of nurses in the ICU is a condition that can be a burden or obstacle for nurses in providing quality nursing care for critical patients who are being treated in the ICU. This study identified the incidence of physical fatigue experienced by nurses in intesive care room. The research was conducted by using a survey using a population of nurses in the ICU room at the RSUD Martapura and RSUD Idaman Banjarbaru using cluster sampling. The results showed that most of the nurses at Martapura Hospital experienced moderate psychological fatigue and the majority of Banjarbaru Hospital nurses experienced mild The nurse management.must have right strategy to reduce the workload and prevent fatigue on nurses to increase quality care in ICU.